cFos mediates cAMP-dependent generation of ROS and rescue of maturation program in retinoid-resistant acute promyelocytic leukemia cell line NB4-LR1. - Jean-Luc Carrier; Pasha Javadi; Emilie Bourrier; Céline Camus; Evelyne Ségal-Bendirdjian; Aïda Karniguian (PLoS ONE, 2012)
A determining role has been assigned to cAMP in the signaling pathways that relieve resistance to anti-leukemia differentiation therapy. However, the underlying mechanisms have not been elucidated yet. Here, we identify cFos as a critical cAMP effector, able to regulate the re-expression and splicing of epigenetically silenced genes associated with maturation (CD44) in retinoid-resistant NB4-LR1 leukemia cells. Furthermore, using RNA interference approach, we show that cFos mediates cAMP-induced ROS generation, a critical mediator of neutrophil maturation, and in fine differentiation. This study highlights some of the mechanisms by which cAMP acts to overcome resistance, and reveals a new alternative cFos-dependent pathway which, though nonexistent in retinoid-sensitive NB4 cells, is essential to rescue the maturation program of resistant cells.